A new species from Turkey, Silene bilgilii (Caryophyllaceae) - Doğan Güner, Ebru; Duman, Hayri (Phytotaxa, 2016)
Silene bilgilii (Caryophyllaceae) from the West Anatolia (province of Balıkesir) is described as a new species. It is morphologically close to S. inclinata and S. leptoclada, from which clearly differs in indumentum, inflorescence and flowers (calyx, corolla and filaments). A distribution map, habitat and ecological remarks, conservation status, and seed micromorphology of the new species are provided.